Community-based Alcohol De-addiction Camp: Participant’s Characteristics and Alcohol Use Pattern - Pradeep Kumar PC; Megha Sadashiv; Kishor M; PJ Princy; Manoj K Pandey (Archives of Medicine and Health Sciences)
Background and Aim: The prevalence of alcohol use in India is ranged from 3.8% to 65.8%. One in every five alcohol users needs treatment. Lack of knowledge about the ill effects of alcohol and an 83% of treatment gap increase the risk. Among many available strategies, community-based alcohol de-addiction camps (ADCs) can offer support to alcohol users. This study aims to assess the participants’ sociodemographic characteristics and alcohol use patterns in alcohol users attending an ADC. Materials and Methods: This cross-sectional descriptive study was conducted at ADC in September 2022. Data from 58 participants were collected using a sociodemographic and clinical data sheet and the alcohol use disorder identification test. Results: The majority of participants voluntarily attended the camp and were aged between 25 and 45 years (67.2%). Most were married (79.3%), had completed secondary education (34.5%), worked as farmers (36.3%), and had a monthly income of INR 6000–18,000 (56.9%). Regarding alcohol use patterns, the majority were daily users (84.5%) for over 5 years (51.7%) and had severe alcohol dependence (86.2%). More than half of the participants had a previous attempt to quit (58.6%) and cited family (51.72%) as a primary reason, followed by health and social respect (48.24%) to quit alcohol. Conclusions: Men aged <45 years with severe alcohol dependence and with previous attempts to quit are likely to utilize the ADC. ADCs may be employed more frequently to effectively address alcohol problems in India.